2021
DOI: 10.1111/epi.17019
|View full text |Cite
|
Sign up to set email alerts
|

Two‐trajectory laser amygdalohippocampotomy: Anatomic modeling and initial seizure outcomes

Abstract: Objective: Laser interstitial thermal therapy (LITT) for mesial temporal lobe epilepsy (mTLE) is typically performed with one trajectory to target the medial temporal lobe (MTL). MTL structures such as piriform and entorhinal cortex are epileptogenic, but due to their relative geometry, they are difficult to target with one trajectory while simultaneously maintaining adequate ablation of the amygdala and hippocampus. We hypothesized that a two-trajectory approach could improve ablation of all relevant MTL stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…40 Another analysis of 28 patients found that patients with Engel I outcomes had a higher percentage of PHG ablated, 41 and a recent study of 11 patients undergoing a two-trajectory approach to target the piriform and entorhinal cortex suggested improved outcomes. 42 Conversely, other studies have found no correlation with ablation of these regions and outcome. 43,44 Some centers now use two fibers including an oblique lateral entry point to cover the amygdala and entorhinal cortex.…”
Section: Discussionmentioning
confidence: 95%
“…40 Another analysis of 28 patients found that patients with Engel I outcomes had a higher percentage of PHG ablated, 41 and a recent study of 11 patients undergoing a two-trajectory approach to target the piriform and entorhinal cortex suggested improved outcomes. 42 Conversely, other studies have found no correlation with ablation of these regions and outcome. 43,44 Some centers now use two fibers including an oblique lateral entry point to cover the amygdala and entorhinal cortex.…”
Section: Discussionmentioning
confidence: 95%
“…In the recently published study, Liu et al. showed that additional trajectory to achieve more extensive ablation of hippocampus, amygdala, and PiC in LITT procedures is more likely associated with seizure freedom 20 . Despite the progress in the field of minimally invasive surgical techniques, the selective epilepsy surgery procedures including tsSAHE remain effective and safe treatment options in mTLE.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed how a two-trajectory laser amygdalohippocampotomy including hippocampus, amygdala, and piriform/entorhinal/perirhinal cortex was superior in full ablation and seizure outcomes. 12 This more extensive ablation including the PC was correlated with the outcome of seizure freedom. Hwang et al performed preablation and postablation volumetric analyses of hippocampus, amygdala, PC, and ablation volumes in 39 patients with mTLE who underwent LITT and found that with multivariable logistic regression only percent PC ablation was a significant predictor of seizure freedom at 6 months (Odds Ratio (OR) 1.085, 95% Confidence Interval (CI) [1.012-1.193], P = .019) and at 1 year (OR 1.074, 95% CI [1.003-1.178], P = .041).…”
Section: Commentarymentioning
confidence: 99%